An Improved Ensemble Deep Learning Model Based on CNN for Malicious Website Detection - Do N.Q.; Selamat A.; Lim K.C.; Krejcar O. (Springer Science and Business Media Deutschland GmbH, 2023)
Computer crime; Convolution; Convolutional neural networks; Cybersecurity; Learning algorithms; Learning systems; Recurrent neural networks; Bidirectional gated recurrent unit; Convolutional neural network; Cyber security; Deep learning; Learning models; Malicious website; Model-based OPC; Phishing detections; Phishing websites; Websites